2020
DOI: 10.1002/ar.24454
|View full text |Cite
|
Sign up to set email alerts
|

Small interfering RNA target for long noncoding RNA PCGEM1 increases the sensitivity of LNCaP cells to baicalein

Abstract: The objective of this study is to investigate the inhibitory effect and mechanism of long noncoding RNA PCGEM1 siRNA combined with baicalein on prostate cancer LNCaP cells. LNCaP cells transfected with small hairpin RNA lentiviral vector targeting PCGEM1 were constructed and their expression in LNCaP cells was absent. The stable cell line of LNCaP cells infected with LV3‐shRNA‐PCGEM1 was successfully constructed. In addition, LV3‐shRNA‐PCGEM1 was able to increase the baicalein‐induced inhibitory effects on LNC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…Baicalein inhibited the proliferation of MCF-7 and MDA-MB-231 breast cancer cells, Fro undifferentiated thyroid cancer cells, and MGC-803 gastric cancer cells, and induced apoptosis and autophagy. It downregulated the expression of downstream proteins phosphorylated Akt (p-AKT), phosphorylated mTOR (p-mTOR), NF-κB, and phosphorylation of inhibitor of kappa B (p-IκB), which play a regulatory role in autophagy, apoptosis, and tumor growth [ 50 , 51 , 146 ]. Drp1-dependent mitochondrial fission is an early and key event of apoptosis, while excessive division will lead to mitochondrial dysfunction, apoptosis, and autophagy.…”
Section: Crosstalk Between Autophagy and Apoptosismentioning
confidence: 99%
“…Baicalein inhibited the proliferation of MCF-7 and MDA-MB-231 breast cancer cells, Fro undifferentiated thyroid cancer cells, and MGC-803 gastric cancer cells, and induced apoptosis and autophagy. It downregulated the expression of downstream proteins phosphorylated Akt (p-AKT), phosphorylated mTOR (p-mTOR), NF-κB, and phosphorylation of inhibitor of kappa B (p-IκB), which play a regulatory role in autophagy, apoptosis, and tumor growth [ 50 , 51 , 146 ]. Drp1-dependent mitochondrial fission is an early and key event of apoptosis, while excessive division will lead to mitochondrial dysfunction, apoptosis, and autophagy.…”
Section: Crosstalk Between Autophagy and Apoptosismentioning
confidence: 99%
“…silenced PCGEM1 in LNCaP prostate cells and treated them with baicalein. They found that reducing PCGEM1 expression enhanced the inhibitory effect of baicalein on tumor cell proliferation and colony formation, induced apoptosis and autophagy and increased the sensitivity of LNCaP cells to baicalein 58 . However, more research is needed to understand the relationship between PCGEM1, baicalein sensitivity or drug resistance and tumor cell autophagy, as well as the specific regulatory mechanism (Figure 5).…”
Section: Lncrna Participates In the Generation Of Anti‐cancer Drug Re...mentioning
confidence: 99%
“…However, some researchers have also observed that autophagy was inhibited in DOX-resistant neuroblastoma, 56 paclitaxel (PTX)-resistant breast cancer 57 and baicalein-resistant prostate cancer. 58 There are many different types of anti-tumour drugs, including cytotoxic drugs that can affect DNA structure and function, interfere with nucleic acid biosynthesis, transcriptional processes, RNA synthesis and protein synthesis and function. There are also non-cytotoxic anti-tumour drugs, such as Tamoxifen (TAM), for ERpositive breast cancer and certain molecularly targeted drugs.…”
Section: Lncrna Participates In the Generation Of Anti-cancer Drug Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the important roles by which PCGEM1 facilitates PC progression in an AR-dependent or AR-independent manner, PCGEM1-targeted treatment is also an attractive area of study. For example, PCGEM1 silencing could increase the sensitivity of PC cells to baicalein and enzalutamide ( 51 , 55 ), laying the groundwork for PC combination therapy. Further clinical trials are needed to design and assess the therapeutic effects of targeting PCGEM1.…”
Section: Clinical Prospects Of Pcgem1mentioning
confidence: 99%